Optimal energy generation with biomass of sugarcane harvest - Homem, T. P D [UNESP]; Balbo, A. R. [UNESP]; Florentino, H. O. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
The aim of this work is the application of the Interior Point and Branch and Bound methods in multiobjective optimization models related to sugarcane harvest residual biomass. These methods showed their viability to help on choosing the sugarcane planting varieties, searching to optimize cost and energy balance of harvest residual biomass, which have conflitant objectives. These methods provide satisfactory results, with fair computing performance and reliable and consistent solutions to the analyzed models. © 2011 IEEE.
Keywords: Computing performance; Interior point; Multi-objective optimization models; Optimal energy; Residual biomass; Biomass; Branch and bound method; Harvesting; Linear programming; Multiobjective optimization; Energy harvesting